The specialized component of pharmaceutical care: access to high-cost medication (Research, Society and Development, 2022)
Introduction: Health in Brazil is a right legally guaranteed by the Federal Constitution of 1988, which established the SINGLE HEALTH SYSTEM (SUS). According to Law 8.080/1990, Pharmaceutical Assistance is included in the field of action of the unified health system. Objective: To discuss the Specialized Component of Pharmaceutical Assistance and clarify the pharmacist's attributions, addressing practices and determinations of the Ministry of Health. Methodology: A descriptive systematic review study was carried out, based on articles and publications from the Ministry of Health, following the PRISMA criteria. Articles published between the years 2000 and 2022 and normative acts in force were used. Results and Discussions: References were obtained from 13 normative acts that are still in force and from 13 articles that were published between the years 2000 and 2022. It was observed that non-adherence to the PCDT and the procedures that the Ministry of Health determines in the Normative Act specific, directly influence the therapy of users. It describes the difficulties of users and professionals with the Centralization of Services and health. Conclusion: Access to high-cost medication at CEAF undergoes careful assessments and its availability occurs through the pharmacist present who follows clinical protocols made available by the ministry of health. It is an ethical duty of the pharmacist to provide the necessary guidance to the user, aiming at the guarantee, safety and effectiveness of the therapy, always observing the rational use of the drug.